Quantitative Detection of miRNA-21 Expression in Tumor Cells and Tissues Based on Molecular Beacon - Qingxin Liu; Jialong Fan; Chuang Zhou; Liqun Wang; Bin Zhao; Haibin Zhang; Bin Liu; Chunyi Tong (International Journal of Analytical Chemistry)
As a new tumor marker, the microRNA-21 (miRNA21) level can provide important information for early diagnosis, drug treatment, and prognosis of gastric cancer. With the tool of molecular beacons which can hybridize specifically with target miRNA-21 and generate fluorescence signal change, this paper develops a direct, simple, and rapid method for miRNA-21 detection with detection limit of 0.5 nM. Under the optimal conditions, the method was used to detect the expression of miRNA-21 in tumor cells and tissues. The results showed significant differences of miRNA-21 levels in tumor cells which have different origins and different degree of malignancy. In 8 cases of gastric cancer tissues and adjacent tissues, the level of miRNA-21 in 6 cases was higher than that in adjacent tissues, 1 case had lower expression level than that in adjacent tissues, and 1 case had no significant difference. Furthermore, qRT-PCR method was used to verify the detection results based on the fluorescent probe detection method. The consistent results show that the molecular beacon assay has a good prospect in direct and rapid detection of miRNA-21 expression and will be widely used in the functional research and clinical diagnosis of microRNA.